Highly adhesive interface mortar and method for its production

CN122977802APending Publication Date: 2026-10-27JIANGSU YINGJU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611219795.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]然而,该技术方案仅验证了25次冻融循环后的粘结强度,对于寒冷地区(年冻融循环可达80~120次)的长期服役需求,其抗冻融性能缺乏保障

Benefits of technology

1、本申请通过采用丙烯酸酯共聚物对硅粉进行核壳包覆,核壳结构使硅粉以独立微球形式均匀分布于砂浆中,有助于减少团聚。分散均匀的硅粉在水化后期能均匀参与火山灰反应,形成全域性的界面过渡区密实效果,有助于提升拉伸粘结强度。丙烯酸酯共聚物的玻璃化转变温度(Tg)低于0℃,在常温下壳层处于玻璃态,对水分和离子的渗透具有阻隔作用,硅粉基本不释放。随着水泥水化放热使体系温度升高至40~60℃,壳层逐渐软化转变为高弹态,透水性和离子渗透性显著增加,硅粉得以逐步释放。这种温度响应型释放机制,在早期(0~24h),壳层完整,硅粉不参与反应,孔隙液pH值维持平稳,避免了对防腐涂层的早期碱冲击;在中期(3~7d),壳层逐渐软化,硅粉开始缓慢释放,参与火山灰反应;在后期(28d以后),硅粉充分反应,孔隙液pH值可以平稳降低。这种渐进式降碱过程,有效保障了与有机防腐涂层的长期化学兼容性。而且,壳层的丙烯酸酯共聚物本身是一种柔性聚合物,分布在水泥石与骨料界面处时,形成微型应力缓冲垫,有效缓解钢材与砂浆因温差产生的热膨胀不匹配应力,提升抗裂性和冻融耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786331288297-000001
    Figure REF-OBJ-1786331288297-000001
Patent Text Reader

Abstract

The application relates to the technical field of building materials, and particularly discloses a high-adhesion interface mortar and a preparation method. The high-adhesion interface mortar comprises the following components in mass parts: composite cementing material 250-650 parts, fine aggregate 350-750 parts, functional core-shell composite microspheres 50-120 parts, epoxy-based modified latex powder 10-40 parts, loaded slow-release microcapsules 8-30 parts, anti-cracking fibers 0.8-3.5 parts, composite water-repellent agent 1.2-6.0 parts, water-retention thickening agent 0.3-2.5 parts, defoaming agent 0.15-1.8 parts and retarder 0.1-1.2 parts; the functional core-shell composite microspheres are core-shell structure microspheres with silica powder as the core and an acrylate copolymer as the shell. The application can maintain the high-adhesion strength and chemical compatibility of the interface mortar, and improve the long-term durability and low-temperature construction adaptability of the interface mortar in a low-temperature application environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of building materials, and in particular to a high-adhesion interface mortar and its preparation method. Background Technology

[0002] Compared with traditional housing, steel-structured houses have significant advantages in structural performance, functionality, design and construction, and overall cost. Developing steel-structured housing is beneficial to promoting technological progress in the construction industry and the transformation and upgrading of the metallurgical industry. The building envelope is one of the core systems of a steel-structured house, and its construction inevitably requires the composite of multiple materials. Due to the significant differences in the interfacial properties between the base layer and the surface layer materials, the bond strength between them often fails to meet practical usage requirements. Therefore, interface mortar becomes an indispensable and crucial bonding layer in the building envelope system.

[0003] Compared to concrete and masonry substrates, steel structure substrates with organic anti-corrosion coatings have the following significantly different characteristics: extremely high surface density, extremely smooth surface, almost no water absorption, and very weak mechanical bonding strength. Therefore, steel structures have special requirements for interface mortars. Traditional interface mortars used in concrete or masonry structures are not suitable for steel structures with organic anti-corrosion coatings, as their bonding performance cannot meet the requirements. Furthermore, interface mortars used for exterior walls must also consider long-term durability issues such as rainwater wetting, freeze-thaw cycles, and the decrease in tensile bond strength after thermal aging.

[0004] In related technologies, Chinese patent CN109020370A discloses an interface mortar formula, which adopts a system of cement, sand, redispersible latex powder, water-repellent agent, defoamer and cellulose ether to achieve basic adhesion with anti-corrosion coating.

[0005] However, this technical solution only verified the bond strength after 25 freeze-thaw cycles. For long-term service requirements in cold regions (where annual freeze-thaw cycles can reach 80-120), its freeze-thaw resistance is not guaranteed. Under repeated freeze-thaw stress, ordinary cement stone experiences continuous microcrack expansion, eventually leading to strength loss and even detachment. Furthermore, cement hydration produces a large amount of calcium hydroxide, and the pore fluid pH can reach 12-13, which, with prolonged contact, may cause chemical corrosion and aging of organic anti-corrosion coatings such as epoxy resin and polyurethane.

[0006] To address the aforementioned issues, there is an urgent need to develop an interface mortar with high bonding strength, good chemical compatibility, excellent long-term durability in low-temperature application environments, and adaptability to low-temperature construction. Summary of the Invention

[0007] In order to improve the long-term durability and low-temperature construction adaptability of interface mortar while maintaining its high bonding strength and chemical compatibility, this application provides a high-bonding interface mortar and its preparation method.

[0008] Firstly, this application provides a high-adhesion interface mortar, which adopts the following technical solution: A high-adhesion interface mortar comprises the following components in parts by weight: 250-650 parts of composite cementitious material, 350-750 parts of fine aggregate, 50-120 parts of functional core-shell composite microspheres, 10-40 parts of epoxy-modified latex powder, 8-30 parts of supported sustained-release microcapsules, 0.8-3.5 parts of crack-resistant fiber, 1.2-6.0 parts of composite water-repellent agent, 0.3-2.5 parts of water-retaining thickener, 0.15-1.8 parts of defoamer, and 0.1-1.2 parts of retarder; wherein the functional core-shell composite microspheres are core-shell structured microspheres with silica powder as the core and acrylate copolymer as the shell.

[0009] In one specific feasible implementation, the functional core-shell composite microspheres are prepared according to the following steps: Silicon powder with a solid content of 25% to 35% is dispersed in deionized water, and polycarboxylic acid dispersant of 0.3% to 0.8% by weight of silicon powder is added and stirred evenly to form a suspension. Under stirring conditions, an acrylate copolymer emulsion was added to the suspension, the pH was adjusted to 8-9, and the mixture was spray-dried to obtain core-shell structured composite microspheres.

[0010] In one specific embodiment, the polymer dry weight of the acrylate copolymer emulsion is 15% to 30% of the mass of the silica powder.

[0011] In one specific feasible implementation, the supported sustained-release microcapsules are prepared according to the following steps: Calcium formate and sodium nitrite were mixed evenly at a mass ratio of (1.5-3):1 to obtain a saturated solution of the composite additive. The porous carrier is placed in a vacuum mixer and evacuated to -0.08 to -0.095 MPa for 20 to 40 minutes. A saturated solution of composite additives is injected, the vacuum is released and the pressure is increased to 0.3 to 0.6 MPa. The carrier is held under pressure for 1 to 3 hours and then centrifuged to remove water, thus obtaining a wet material loaded with additives. The wet material loaded with additives was placed in a fluidized bed, and a paraffin microemulsion was sprayed by atomization. The mixture was then dried and fluidized under hot air at 60-80℃ to obtain loaded sustained-release microcapsules.

[0012] In one specific feasible implementation, the amount of the paraffin microemulsion is 2% to 8% of the mass of the porous carrier.

[0013] In one specific implementation, the porous carrier of the supported sustained-release microcapsules is zeolite powder or fly ash hollow microspheres.

[0014] In one specific implementation, the composite cementitious material comprises silicate cement and sulfoaluminate cement in a mass ratio of (3-9):2.

[0015] In one specific feasible implementation, the fine aggregate is 40-140 mesh quartz sand.

[0016] In one specific implementation, the crack-resistant fiber comprises polypropylene short fibers and basalt short fibers in a mass ratio of (0.6 to 0.8):1.

[0017] Secondly, this application provides a method for preparing a high-adhesion interface mortar, which adopts the following technical solution: A method for preparing a high-adhesion interface mortar includes the following steps: The composite cementitious material, fine aggregate, and crack-resistant fiber are mixed evenly, and then core-shell composite microspheres, epoxy-modified latex powder, supported slow-release microcapsules, composite water-repellent agent, water-retaining thickener, defoamer, and retarder are added. The mixture is stirred until homogeneous to obtain a highly adhesive interface mortar.

[0018] In summary, this application has the following beneficial effects: 1. This application employs an acrylate copolymer to encapsulate silica powder in a core-shell structure. This core-shell structure allows the silica powder to be uniformly distributed in the mortar as independent microspheres, helping to reduce agglomeration. The uniformly dispersed silica powder can participate evenly in the pozzolanic reaction during the later stages of hydration, forming a dense interfacial transition zone that helps improve tensile bond strength. The glass transition temperature (Tg) of the acrylate copolymer is below 0℃. At room temperature, the shell layer is in a glassy state, acting as a barrier to the penetration of moisture and ions, and the silica powder is essentially not released. As the temperature of the system rises to 40–60℃ due to the exothermic reaction of cement hydration, the shell layer gradually softens and transforms into a highly elastic state, significantly increasing water permeability and ion permeability, allowing the silica powder to be gradually released. This temperature-responsive release mechanism ensures that in the early stage (0–24 h), the shell layer remains intact, silica fume does not participate in the reaction, and the pH value of the pore liquid remains stable, avoiding early alkaline shock to the anti-corrosion coating. In the middle stage (3–7 days), the shell layer gradually softens, and silica fume begins to be released slowly, participating in the pozzolanic reaction. In the later stage (after 28 days), the silica fume reacts fully, and the pH value of the pore liquid can decrease steadily. This gradual alkali reduction process effectively ensures long-term chemical compatibility with the organic anti-corrosion coating. Moreover, the acrylate copolymer in the shell layer is itself a flexible polymer. When distributed at the interface between cement stone and aggregate, it forms a micro-stress buffer pad, effectively alleviating the thermal expansion mismatch stress caused by temperature difference between steel and mortar, and improving crack resistance and freeze-thaw durability.

[0019] 2. This application employs supported slow-release microcapsules. Zeolite powder or fly ash hollow microspheres possess a well-developed microporous structure. Vacuum pressure impregnation allows the admixture solution to fully penetrate the pores, achieving physical adsorption. Physical adsorption itself has a certain slow-release effect, but the release rate is still relatively fast. Paraffin microemulsions have a melting point of 50–65℃. In the initial stage of water mixing, the system temperature is below the paraffin melting point, the sealing layer remains intact, preventing mixing water from entering the carrier pores, and the admixture is essentially not released. As the cement hydration releases heat, the system temperature gradually rises above the paraffin melting point, the sealing layer melts and softens, allowing mixing water to enter the pores and dissolve the admixture, which is then continuously released over 8–72 hours. This time-series control mechanism of no early release followed by slow release after temperature rise ensures continuous cement hydration under low-temperature conditions, avoiding early freezing damage. Furthermore, the continuous supply of sodium nitrite during low-temperature periods continuously lowers the freezing point of the mixing water, preventing frost heave stress from damaging the mortar structure and maintaining a high strength level after freeze-thaw cycles.

[0020] 3. The paraffin sealing layer on the surface of each sustained-release microcapsule in this application is itself a microscopic hydrophobic node. After being evenly distributed in the mortar, it forms a three-dimensional waterproof structure with the composite water-repellent agent, which helps to significantly reduce the water absorption rate, reduce the content of freezeable water from the source, and further improve the freeze-thaw resistance.

[0021] 4. This application uses a composite cementitious material with a limited raw material ratio. The synergistic effect of sulfoaluminate cement and sulfoaluminate cement can reduce the generation of microcracks and rapidly build up early strength at low temperatures.

[0022] 5. This application uses crack-resistant fibers with a limited raw material ratio, and polymer fibers and basalt fibers work together to form a multi-level stress dissipation network with micro-flexible buffer and macro-rigid enhancement, so that the frost heave stress generated by freeze-thaw cycles is dissipated step by step, thereby greatly increasing the number of freeze-thaw cycles. Detailed Implementation

[0023] Unless otherwise specified, all raw materials used in this application are commercially available. The silicate cement is P·O 42.5 grade ordinary silicate cement, and the sulfoaluminate cement is 42.5 grade rapid-hardening sulfoaluminate cement. Epoxy-modified latex powder, model: Wacker NEXIVA® CT 115. Hydroxyethyl methyl cellulose ether, model: Hercules HEMC 60K. Polyether-modified silicone defoamer, model: Zhongwei DYFOMA™ 308. Sodium gluconate, purity ≥98%. Polypropylene short fiber, standard: GB / T21120 "Synthetic Fibers for Cement Concrete and Mortar", length 6mm. Basalt short fiber, standard: GB / T 23265 "Short-cut Basalt Fibers for Cement Concrete and Mortar", length 12mm. Silyl-based powdered water-repellent agent, model: Dow Corning SHP-50. Calcium stearate, purity ≥98%. Silica powder, brand: Elkem 940. Polycarboxylate dispersant, model: Jiarun RN-40S. Acrylic ester copolymer emulsion, model: Wacker PRIMIS® SAF 9000. Calcium formate, purity ≥98%. Sodium nitrite, purity ≥98%. Zeolite powder, natural zeolite powder from Chifeng area, particle size ≤75μm. Paraffin microemulsion, Clariant paraffin emulsion, solid content 40-60%. Fly ash hollow microspheres, particle size ≤75μm, purchased from Lingshou County Wanzhu Mineral Products Co., Ltd.

[0024] The present application will be further described in detail below with reference to embodiments and comparative examples.

[0025] Example 1

[0026] This embodiment provides a high-adhesion interface mortar, comprising the following components: 450 kg of composite cementitious material, 550 kg of fine aggregate, 85 kg of functional core-shell composite microspheres, 25 kg of epoxy-modified latex powder, 19 kg of supported sustained-release microcapsules, 2.2 kg of crack-resistant fiber, 3.6 kg of composite water-repellent agent, 1.4 kg of hydroxyethyl methyl cellulose ether, 1 kg of polyether-modified silicone defoamer, and 0.6 kg of sodium gluconate.

[0027] The composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of 3:1. The fine aggregate is 40-140 mesh quartz sand. The crack-resistant fibers include polypropylene short fibers and basalt short fibers in a mass ratio of 0.7:1. The composite water-repellent agent includes silane powder water-repellent agent and calcium stearate in a mass ratio of 3:2.

[0028] Functional core-shell composite microspheres were prepared according to the following steps: Silicon powder with a solid content of 30% was dispersed in deionized water, and polycarboxylic acid dispersant with a mass of 0.55% of the silicon powder was added. The mixture was stirred for 30 minutes to form a suspension.

[0029] The dry weight of the acrylate copolymer emulsion was adjusted to 22.5% of the silica powder mass using deionized water. Under stirring conditions, the adjusted acrylate copolymer emulsion was added to the suspension, the pH was adjusted to 8.5, and spray drying was performed using a centrifugal spray dryer with an inlet temperature of 150℃ and an outlet temperature of 80℃ to obtain core-shell structured composite microspheres.

[0030] The supported sustained-release microcapsules were prepared according to the following steps: Calcium formate and sodium nitrite were mixed evenly at a mass ratio of 2.25:1 to obtain a saturated solution of the composite additive.

[0031] Zeolite powder was placed in a vacuum mixer, vacuumed to -0.09 MPa, and degassed for 30 minutes; a saturated solution of composite additives was injected, the vacuum was released and pressurized to 0.5 MPa, and impregnated under pressure for 2 hours. After centrifugation and dehydration, wet material loaded with additives was obtained.

[0032] A wet material loaded with additives was placed in a fluidized bed, and a paraffin microemulsion was atomized and sprayed onto it. The mixture was then dried and fluidized under hot air at 70°C to obtain loaded sustained-release microcapsules. The amount of paraffin microemulsion used was 5% of the mass of the zeolite powder.

[0033] This embodiment also provides a method for preparing a high-adhesion interface mortar, including the following steps: The composite cementitious material, fine aggregate, and crack-resistant fiber are mixed evenly, and then core-shell composite microspheres, epoxy-modified latex powder, supported slow-release microcapsules, composite water-repellent agent, hydroxyethyl methyl cellulose ether, polyether-modified organosilicon defoamer, and sodium gluconate are added. The mixture is stirred until homogeneous to obtain a high-adhesion interface mortar.

[0034] Example 2

[0035] The only difference between this embodiment and Embodiment 1 is that the high-adhesion interface mortar includes the following components: 650 kg of composite cementitious material, 750 kg of fine aggregate, 120 kg of functional core-shell composite microspheres, 40 kg of epoxy-modified latex powder, 30 kg of supported sustained-release microcapsules, 3.5 kg of crack-resistant fiber, 6.0 kg of composite water-repellent agent, 2.5 kg of hydroxyethyl methyl cellulose ether, 1.8 kg of polyether-modified silicone defoamer, and 1.2 kg of sodium gluconate.

[0036] Example 3

[0037] The only difference between this embodiment and Embodiment 1 is that the high-adhesion interface mortar includes the following components: 250 kg of composite cementitious material, 350 kg of fine aggregate, 50 kg of functional core-shell composite microspheres, 10 kg of epoxy-modified latex powder, 8 kg of supported sustained-release microcapsules, 0.8 kg of crack-resistant fiber, 1.2 kg of composite water-repellent agent, 0.3 kg of hydroxyethyl methyl cellulose ether, 0.15 kg of polyether-modified silicone defoamer, and 0.1 kg of sodium gluconate.

[0038] Example 4

[0039] The only difference between this embodiment and Embodiment 1 is that the composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of 1:1.

[0040] Example 5

[0041] The only difference between this embodiment and Embodiment 1 is that the composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of 3:2.

[0042] Example 6

[0043] The only difference between this embodiment and Embodiment 1 is that the composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of 9:2.

[0044] Example 7

[0045] The only difference between this embodiment and Embodiment 1 is that the composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of 6:1.

[0046] Example 8

[0047] The only difference between this embodiment and Embodiment 1 is that the crack-resistant fiber includes polypropylene short fibers and basalt short fibers in a mass ratio of 0.5:1.

[0048] Example 9

[0049] The only difference between this embodiment and Embodiment 1 is that the crack-resistant fiber includes polypropylene short fibers and basalt short fibers in a mass ratio of 0.6:1.

[0050] Example 10

[0051] The only difference between this embodiment and Embodiment 1 is that the crack-resistant fiber includes polypropylene short fibers and basalt short fibers in a mass ratio of 0.8:1.

[0052] Example 11

[0053] The only difference between this embodiment and Embodiment 1 is that the crack-resistant fiber includes polypropylene short fibers and basalt short fibers in a mass ratio of 0.9:1.

[0054] Example 12

[0055] The only difference between this embodiment and Example 1 is that the functional core-shell composite microspheres are prepared according to the following steps: Silicon powder with a solid content of 25% was dispersed in deionized water, and polycarboxylic acid dispersant with a mass of 0.3% of silicon powder was added. The mixture was stirred for 30 minutes to form a suspension.

[0056] The dry weight of the acrylate copolymer emulsion was adjusted to 22.5% of the silica powder mass using deionized water. Under stirring conditions, the adjusted acrylate copolymer emulsion was added to the suspension, the pH was adjusted to 8, and spray-dried using a centrifugal spray dryer at an inlet temperature of 150℃ and an outlet temperature of 80℃ to obtain core-shell structured composite microspheres. The dry weight of the acrylate copolymer emulsion was 22.5% of the silica powder mass.

[0057] Example 13

[0058] The only difference between this embodiment and Example 1 is that the functional core-shell composite microspheres are prepared according to the following steps: Silicon powder with a solid content of 35% was dispersed in deionized water, and polycarboxylic acid dispersant with a mass of 0.8% of silicon powder was added. The mixture was stirred for 30 minutes to form a suspension.

[0059] The dry weight of the acrylate copolymer emulsion was adjusted to 22.5% of the silica powder mass using deionized water. Under stirring conditions, the adjusted acrylate copolymer emulsion was added to the suspension, the pH was adjusted to 9, and spray-dried using a centrifugal spray dryer at an inlet temperature of 150℃ and an outlet temperature of 80℃ to obtain core-shell structured composite microspheres. The dry weight of the acrylate copolymer emulsion was 22.5% of the silica powder mass.

[0060] Example 14

[0061] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the functional core-shell composite microspheres, the dry weight of the acrylate copolymer emulsion is adjusted to 12.5% ​​of the mass of the silica powder using deionized water.

[0062] Example 15

[0063] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the functional core-shell composite microspheres, the dry weight of the acrylate copolymer emulsion is adjusted to 15% of the mass of the silicon powder using deionized water.

[0064] Example 16

[0065] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the functional core-shell composite microspheres, the dry weight of the acrylate copolymer emulsion is adjusted to 30% of the mass of the silica powder using deionized water.

[0066] Example 17

[0067] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the functional core-shell composite microspheres, the dry weight of the acrylate copolymer emulsion is adjusted to 32.5% of the mass of the silica powder using deionized water.

[0068] Example 18

[0069] The only difference between this embodiment and Example 1 is that the supported sustained-release microcapsules are prepared according to the following steps: Calcium formate and sodium nitrite were mixed evenly at a mass ratio of 1.5:1 to obtain a saturated solution of the composite additive.

[0070] Zeolite powder was placed in a vacuum mixer and evacuated to -0.08 MPa for 20 minutes. A saturated solution of composite additives was then injected, the vacuum was released and the pressure was increased to 0.3 MPa. The mixture was held under pressure for 1 hour and then centrifuged to remove water, resulting in a wet material loaded with additives.

[0071] A wet material loaded with additives was placed in a fluidized bed, and a paraffin microemulsion was atomized and sprayed onto it. The mixture was then dried and fluidized under hot air at 60°C to obtain loaded sustained-release microcapsules. The amount of paraffin microemulsion used was 5% of the mass of the zeolite powder.

[0072] Example 19

[0073] The only difference between this embodiment and Example 1 is that the supported sustained-release microcapsules are prepared according to the following steps: Calcium formate and sodium nitrite were mixed evenly at a mass ratio of 2.25:1 to obtain a saturated solution of the composite additive.

[0074] Zeolite powder was placed in a vacuum mixer and evacuated to -0.095 MPa for 40 minutes. A saturated solution of composite additives was then injected, the vacuum was released and the pressure was increased to 0.6 MPa. The mixture was then impregnated under pressure for 3 hours and centrifuged to remove water, thus obtaining a wet material loaded with additives.

[0075] A wet material loaded with additives was placed in a fluidized bed, and a paraffin microemulsion was atomized and sprayed onto it. The mixture was then dried and fluidized under hot air at 80°C to obtain supported sustained-release microcapsules. The amount of paraffin microemulsion used was 5% of the mass of the zeolite powder.

[0076] Example 20

[0077] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the supported sustained-release microcapsules, the amount of paraffin microemulsion used is 1% of the mass of zeolite powder.

[0078] Example 21

[0079] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the supported sustained-release microcapsules, the amount of paraffin microemulsion used is 2% of the mass of zeolite powder.

[0080] Example 22

[0081] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the supported sustained-release microcapsules, the amount of paraffin microemulsion used is 8% of the mass of zeolite powder.

[0082] Example 23

[0083] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the supported sustained-release microcapsules, the amount of paraffin microemulsion used is 10% of the mass of zeolite powder.

[0084] Example 24

[0085] The only difference between this embodiment and Embodiment 1 is that, in the preparation step of the supported sustained-release microcapsules, an equal amount of fly ash hollow microspheres are used to replace the zeolite powder.

[0086] Comparative Example 1 The only difference between this comparative example and Example 1 is that the raw materials and preparation method of the high-adhesion interface mortar do not contain functional core-shell composite microspheres.

[0087] Comparative Example 2 The only difference between this comparative example and Example 1 is that the raw materials and preparation method of the high-adhesion interface mortar do not contain epoxy-modified latex powder.

[0088] Comparative Example 3 The only difference between this comparative example and Example 1 is that the raw materials and preparation method of the high-adhesion interface mortar do not contain loaded sustained-release microcapsules.

[0089] Comparative Example 4 The only difference between this comparative example and Example 1 is that, in the raw materials and preparation method of the high-adhesion interface mortar, an equal amount of silicate cement is used to replace the composite cementitious material.

[0090] Comparative Example 5 The only difference between this comparative example and Example 1 is that the raw materials and preparation method of the high-adhesion interface mortar do not contain hydroxyethyl methyl cellulose ether.

[0091] Performance testing The following performance tests were conducted on Examples 1-24 and Comparative Examples 1-5: The interface mortars prepared in each embodiment and comparative example were tested as follows: Referring to JGJ / T 70-2009 and GB / T17671 standards, a steel plate with a medium layer of anti-corrosion paint and a size of 70mm×70mm×10mm was used as the base plate. The interface mortar was mixed with water at a water-to-material ratio of 0.2 and stirred evenly. A mortar layer with a thickness of 3-5mm was applied to the surface of the base plate, with a bonding area of ​​40mm×40mm, to obtain the spare specimens.

[0092] Original strength test: After curing the spare specimens at a temperature of (20±2)℃ and a relative humidity of ≥95% for 28 days, according to JGJ / T 70-2009, the specimens were placed in the tensile testing machine fixtures, and a tensile force was applied at a speed of 5 mm / min. The fixtures were connected to the testing machine by a ball joint. The maximum failure load was recorded and calculated using the following formula: Tensile bond strength (MPa) = Maximum failure load / Bond area The tensile bond strength (original strength, 28d) of the interface mortar in each embodiment and comparative example was calculated.

[0093] Freeze-thaw strength test: Immerse the spare specimen in water at (20±5)℃ for 8 hours (depth 2~10mm), then freeze at (-20±2)℃ for 16 hours to complete one freeze-thaw cycle. After 30, 50, and 100 freeze-thaw cycles respectively, according to JGJ / T 70-2009, place the specimen in the tensile testing machine fixture and apply a tensile force at a speed of 5mm / min. The fixture is connected to the testing machine by a ball joint. Record the maximum failure load and calculate it using the following formula: Tensile bond strength (MPa) = Maximum failure load / Bond area The tensile bond strength (30 freeze-thaw cycles), tensile bond strength (50 freeze-thaw cycles), and tensile bond strength (100 freeze-thaw cycles) of the interface mortar in each embodiment and comparative example were calculated.

[0094] Permeability pressure test: After curing the spare specimens for 28 days at a temperature of (20±2)℃ and relative humidity of ≥95%, the specimens cured for 28 days were placed into the permeability tester according to JC / T 984-2011. The pressure was increased from 0.1MPa, and the water pressure was increased by 0.1MPa every 8 hours. The maximum pressure value of the four specimens in each group of six that did not show water seepage was the permeability pressure.

[0095] Water absorption test: The spare specimens were cured for 28 days at a temperature of (20±2)℃ and a relative humidity ≥95%. Following JGJ / T 70-2009, they were dried in an oven at (105±5)℃ until constant weight (m0). After cooling, they were immersed in water at (20±2)℃ for 24 hours. After removing and drying the surface moisture, the specimens were weighed (m1) and the water absorption rate was calculated using the following formula: Water absorption rate = (m1 - m0) / m0 × 100% The water absorption rate of the interface mortar in each embodiment and comparative example was calculated.

[0096] Interface alkalinity test: After the specimen of the original strength test is destroyed, take 1g of mortar powder in the interface area, add deionized water at a solid-liquid ratio of 1:10, stir thoroughly and let stand for 24h, and use a pH meter to measure the pH value of the supernatant to obtain the pH value of the interface area.

[0097] The test results are shown in Table 1.

[0098] Table 1

[0099] Combining Example 1 and Comparative Examples 1-5 with Table 1, it can be seen that, compared to Example 1, the silica powder in Comparative Example 1 was directly incorporated in ordinary form, resulting in severe agglomeration and uneven dispersion, insufficient volcanic ash reaction, a high pH value of 12.8 at the interface, and a strength of only 0.4 MPa after 30 freeze-thaw cycles, with detachment after 50 cycles. This demonstrates the decisive role of the core-shell structure in silica powder dispersion and gradual alkali reduction. Comparative Example 2 lacked epoxy-modified latex powder, and its bonding strength dropped sharply to 0.4 MPa after immersion in water, detaching after 50 freeze-thaw cycles. This demonstrates the key contribution of epoxy-modified latex powder to wet bonding durability. In Comparative Example 3, calcium formate and sodium nitrite were directly incorporated in ordinary powder form, dissolving instantly upon addition of water, with a short effective action time at low temperatures, detaching after 100 freeze-thaw cycles. This demonstrates the decisive role of the supported slow-release microcapsules in low-temperature construction and long-term freeze resistance. Comparative Example 4 used only ordinary silicate cement, which hydrated slowly at low temperatures, detaching after 50 freeze-thaw cycles. This demonstrates the crucial role of sulfoaluminate cement in achieving early strength at low temperatures. Comparative Example 5, lacking hydroxyethyl methyl cellulose ether, exhibited insufficient water retention, a strength retention rate of only 60% after 60 minutes of workability, poor workability, and a water absorption rate increased to 6.2%. This highlights the importance of hydroxyethyl methyl cellulose ether for both workability and water retention.

[0100] As can be seen from Examples 1-24 and Table 1, Examples 1, 16, and 22 have higher tensile bond strengths, while Example 14 has a lower tensile bond strength. However, the tensile bond strengths of Examples 1-24 are all ≥1.4 MPa.

[0101] After 50 freeze-thaw cycles, the tensile bond strength (after 50 freeze-thaw cycles) of Examples 1, 10, 16, 19, and 22 was ≥1.0 MPa. Comparative Examples 1 and 2 detached after 50 freeze-thaw cycles, which demonstrates the decisive role of core-shell microspheres and epoxy powder in resisting freeze-thaw performance.

[0102] After 100 freeze-thaw cycles, the tensile bond strength (after 100 freeze-thaw cycles) of Examples 1, 10, 16, 19, and 22 was ≥0.8 MPa, while the tensile bond strength (after 100 freeze-thaw cycles) of Comparative Example 5 was 0.5 MPa. The remaining comparative examples detached after 50 or 100 cycles. This demonstrates that the functional core-shell composite microspheres, epoxy-modified latex powder, supported sustained-release microcapsules, composite gelling material, and hydroxyethyl methyl cellulose ether of this application are essential conditions for achieving durability through 100 freeze-thaw cycles, and none of them can be omitted.

[0103] Examples 1 and 16 exhibited the highest anti-permeability pressure, while Example 16 had the lowest water absorption rate. Comparative Example 1 had the lowest anti-permeability pressure and the highest water absorption rate, indicating that the synergistic effect of core-shell structured silica powder and composite hydrophobic agent can significantly reduce water absorption rate.

[0104] The pH value of the interface region in Examples 1, 7, 16, and 22 all decreased to 11.5, while the pH value of the interface region in Comparative Example 1 reached 12.8. This indicates that the progressive pozzolanic reaction of core-shell structured silica powder can effectively reduce the alkalinity of the interface region and improve its chemical compatibility with the anti-corrosion coating.

[0105] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-adhesion interface mortar, characterized in that, The product comprises the following components in parts by weight: 250-650 parts of composite cementitious material, 350-750 parts of fine aggregate, 50-120 parts of functional core-shell composite microspheres, 10-40 parts of epoxy-modified latex powder, 8-30 parts of supported sustained-release microcapsules, 0.8-3.5 parts of crack-resistant fiber, 1.2-6.0 parts of composite water-repellent agent, 0.3-2.5 parts of water-retaining thickener, 0.15-1.8 parts of defoamer, and 0.1-1.2 parts of retarder; wherein the functional core-shell composite microspheres are core-shell structured microspheres with silica powder as the core and acrylate copolymer as the shell.

2. The high-adhesion interface mortar according to claim 1, characterized in that, The functional core-shell composite microspheres were prepared according to the following steps: Silicon powder with a solid content of 25% to 35% is dispersed in deionized water, and polycarboxylic acid dispersant of 0.3% to 0.8% by weight of silicon powder is added and stirred evenly to form a suspension. Under stirring conditions, an acrylate copolymer emulsion was added to the suspension, the pH was adjusted to 8-9, and the mixture was spray-dried to obtain core-shell structured composite microspheres.

3. The high-adhesion interface mortar according to claim 2, characterized in that, The dry weight of the polymer in the acrylate copolymer emulsion is 15% to 30% of the mass of the silica powder.

4. The high-adhesion interface mortar according to claim 1, characterized in that, The supported sustained-release microcapsules were prepared according to the following steps: Calcium formate and sodium nitrite were mixed evenly at a mass ratio of (1.5-3):1 to obtain a saturated solution of the composite additive. The porous carrier is placed in a vacuum mixer and evacuated to -0.08 to -0.095 MPa for 20 to 40 minutes. A saturated solution of composite additives is injected, the vacuum is released and the pressure is increased to 0.3 to 0.6 MPa. The carrier is held under pressure for 1 to 3 hours and then centrifuged to remove water, thus obtaining a wet material loaded with additives. The wet material loaded with additives was placed in a fluidized bed, and a paraffin microemulsion was sprayed by atomization. The mixture was then dried and fluidized under hot air at 60-80℃ to obtain loaded sustained-release microcapsules.

5. The high-adhesion interface mortar according to claim 4, characterized in that, The amount of the paraffin microemulsion used is 2% to 8% of the mass of the porous carrier.

6. The high-adhesion interface mortar according to claim 4, characterized in that, The porous carrier of the loaded sustained-release microcapsules is zeolite powder or fly ash hollow microspheres.

7. The high-adhesion interface mortar according to claim 1, characterized in that, The composite cementitious material includes silicate cement and sulfoaluminate cement in a mass ratio of (3-9):

2.

8. The high-adhesion interface mortar according to claim 1, characterized in that, The fine aggregate is 40-140 mesh quartz sand.

9. The high-adhesion interface mortar according to claim 1, characterized in that, The crack-resistant fiber comprises polypropylene short fibers and basalt short fibers in a mass ratio of (0.6-0.8):

1.

10. A method for preparing a high-adhesion interface mortar as described in any one of claims 1-9, characterized in that, Includes the following steps: The composite cementitious material, fine aggregate, and crack-resistant fiber are mixed evenly, and then core-shell composite microspheres, epoxy-modified latex powder, supported slow-release microcapsules, composite water-repellent agent, water-retaining thickener, defoamer, and retarder are added. The mixture is stirred until homogeneous to obtain a highly adhesive interface mortar.

Citation Information

Patent Citations

  • Interface mortar for steel structural exterior wall with anticorrosive coating layer

    CN109020370A